The Sounds of Development : Musical Representation as A(nother) Source of Development Knowledge - Lewis, David (Taylor and Francis, 2021)
The experience of development, as well as understandings of and responses to it, are uniquely rendered via popular culture generally, and popular music in particular. Music has been a medium of choice through which marginalized populations all over the world convey their (frequently critical) views, while in the Global North music has also long played a prominent (if notorious) role in portraying the plight of the South’s ‘starving millions’ as an emotional pretext for soliciting funds for international aid. We discuss the relationship between music and development in five specific domains: the tradition of Western ‘protest’ music; musical resistance in the Global South; music-based development interventions; commodification and appropriation; and, finally, music as a globalized development vernacular. We present our analyses not as definitive or comprehensive but as invitations to broaden the range of potential contributions to development debates, and the communicative modalities in and through which these debates are conducted. Doing so may lead to enhancing the relevance and coherence of development debates for a greater range of key stakeholders of development by making them more open, authentic, and compelling.